PEMBERDAYAAN PENJAHIT MASKER KAIN ANTI COVID-19 DI KABUPATEN MOJOKERTO - Ilhamuddin, Muhammad Farid (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2021)
Covid 19 pandemic has an impact on Indonesian economy, corona impact is also experienced by people who work as shoes and sandal tailors around Mojokerto city. Their income has decreased because there are no buyers to buy their products. The purpose of this community service activity is to sharing knowledge to the community to be able to make 2 –layers fabric masks, drive the community's economy and support the demand of mask commodities in the prevention of Covid-19. The method is to provide education and training in sewing 2-layer fabric masks. Their sewing skills that they have before make education and training process getting easy, they are previously sewed shoes and sandals now turn to sew cloth masks, cloth masks made from cotton fabrics consists of 2 layers. The supply of medical masks is quite rare and is intended for medical personnel so 2-layers fabric masks are considered capable of suppressing the spread of corona virus. From the results of education and training in sewing and producing masks, data and information were obtained that the people of Mojokerto were able to produce 2-layer fabric masks and run of their economy so that they did not experience significant losses.